From Logic to Rhetoric : Translated from the French original edition, Paris, 1982. - Meyer, Michel (John Benjamins Pub. Co., 1986)
What is language, and how has it been conceived since Frege? How did the development of thought about language lead to a renewed interest in rhetoric in the twentieth century and ultimately to the 'problematological synthesis'? These are the main questions treated in this book. A constant intertwining of historical and topical viewpoints characterizes the author's approach.